Enhanced Stress Tolerance in Rice Through Overexpression of a Chimeric Glycerol-3-Phosphate Dehydrogenase (OEGD) - Jinhong Wu; Meiyao Chen; Fangwen Yang; Jing Han; Xiaosong Ma; Tianfei Li; Hongyan Liu; Bin Liang; Shunwu Yu (Plants)
Crop productivity is severely constrained by abiotic and biotic stresses, necessitating innovative strategies to enhance stress resilience. Glycerol-3-phosphate (G3P) is a central metabolite in carbohydrate and lipid metabolism, playing crucial roles in stress responses. In this study, we engineered a novel glycerol-3-phosphate dehydrogenase (GPDH) gene, designated OEGD, by fusing the N-terminal NAD-binding domain of rice OsGPDH1 with the feedback-resistant C-terminal catalytic domain of Escherichia coli gpsA. Overexpression of OEGD in rice enhanced tolerance to drought, phosphorus deficiency, high temperature, and cadmium (Cd2+) stresses, while also improving plant growth and yield under drought stress at the adult stage. Notably, the accumulation of glycerol-3-phosphate (G3P) and activities of antioxidant enzymes (SOD, POD, CAT) were significantly elevated in the transgenic plants following osmotic stimuli, and fatty acid profiles were altered, favoring stress adaptation. Transcriptomic analyses revealed that OEGD modulates cell wall biogenesis, reactive oxygen species (ROS) scavenging, and lipid metabolism pathways, with minimal disruption to core G3P metabolic genes. These findings highlight the potential of OEGD as a valuable genetic resource for improving stress resistance in rice.